PERCEIVED IMPACTS OF EXAMINATION MISCONDUCT ON ACADEMIC ACHIEVEMENT OF BIOLOGY STUDENTS’ IN AJAOKUTA LOCAL GOVERNMENT AREA OF KOGI STATE (UNIZIK Journal of STM Education, 2024)
This study investigated perceived impacts of Examination Misconduct on Academic Achievement of Biology Students’ in Ajaokuta Local Government Area of Kogi State. Three research questions directed the investigation. Descriptive survey research design was used to carry out this study. The population for the study comprised 3756 SS 11 biology students from the twenty one senior secondary schools in Ajaokuta Local Government Area of Kogi State within 2022/2023 academic session. Simple random sampling techniques were used to select twelve senior secondary schools offering Biology. Consequently, a sample of 306 SS 11 Biology students was used for the study. Structured questionnaire named Perceived Impacts of examination misconduct on academic Achievement of Biology students. (PIEMOAABS) was the instrument used. Reliability was carried out using Cronbach alpha. Reliability Coefficient of 0.86 was obtained. The data collected was analysed using mean and standard deviation to answer the research questions. Results revealed that the causes of examination misconduct among biology students include lack of seriousness among the students and teachers, overloaded biology syllabus, fear of examination failure among others. The impacts among others are rendering the goal of education invalid, production of half-baked graduates and irreversible loss of credibility. It was suggested, among other things, that our children be properly raised with strong moral principles, that parents should stop encouraging their kids to cheat on exams, Once more, only trustworthy individuals should be involved in exam management.
Keywords: Examination Misconduct, Impact, Achievement and Biology